2018
DOI: 10.1371/journal.pmed.1002715
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and acceptability of psychosocial interventions for individuals with cocaine and amphetamine addiction: A systematic review and network meta-analysis

Abstract: BackgroundClinical guidelines recommend psychosocial interventions for cocaine and/or amphetamine addiction as first-line treatment, but it is still unclear which intervention, if any, should be offered first. We aimed to estimate the comparative effectiveness of all available psychosocial interventions (alone or in combination) for the short- and long-term treatment of people with cocaine and/or amphetamine addiction.Methods and findingsWe searched published and unpublished randomised controlled trials (RCTs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
130
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(143 citation statements)
references
References 73 publications
1
130
0
3
Order By: Relevance
“…Therefore, rTMS for CocUD may find its place as an additional tool in settings where psychotherapeutic or behavioral treatments are administered. Meta-analyses have repeatedly shown that the most effective known treatments for CocUD are behavioral ones incorporating both tangible incentives for abstinence and social reinforcement of abstinence (25). rTMS could readily be integrated into those behavioral approaches, to be given as needed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, rTMS for CocUD may find its place as an additional tool in settings where psychotherapeutic or behavioral treatments are administered. Meta-analyses have repeatedly shown that the most effective known treatments for CocUD are behavioral ones incorporating both tangible incentives for abstinence and social reinforcement of abstinence (25). rTMS could readily be integrated into those behavioral approaches, to be given as needed.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these findings highlight the critical need to ensure that individuals are provided with appropriately tailored evidence‐based services. In particular, medications for OUD combined with a contingency management and community reinforcement approach may be an effective clinical strategy for this population. In addition, given the high prevalence of methamphetamine injection and the increased odds of reporting methamphetamine injection among treatment admissions reporting heroin injection, expansion of interventions aimed at reducing injection drug use‐related harms such as implementation of comprehensive syringe services programs (needle and syringe exchange programs) are needed to mitigate additional spread of infectious diseases such as viral hepatitis and HIV and injection drug‐use associated morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Even short periods of intervention with CBT (1-2 sessions) demonstrate a reduction in MA use in people who are dependent on MA [14]. CM has demonstrated significant reduction in stimulant use [16] alone, or in combination with CBT [16] or a community reinforcement approach [17]. However, the effects of psychosocial therapies are often not sustained following their cessation [14,18], and are less effective for severe disorder (long duration, frequent use) [19].…”
Section: Introductionmentioning
confidence: 99%